'Easier to isolate yourself…there's no need to leave the house' – A qualitative study on the paradoxes of online communication for parents with young children. (June 2018) - Strange, Cecily; Fisher, Colleen; Howat, Peter; Wood, Lisa
Abstract: There is a growing body of literature identifying the benefits for families from accessing information and communicating online. What is less investigated and reported is the potential downside of online information, support and networks for parents of young children. Parents with at least one child 0–5 years of age (n = 487) were asked if they felt online communication helped to support families with young children (3 options – yes, no, yes and no), and to provide a supporting statement. Respondents were also asked to indicate the reasons they used Facebook and parenting websites, blogs and forums. A descriptive and content analysis was undertaken. The proposition that online communication helped to support parents of young children was upheld by the majority (n = 302) while 12 responded 'no', 173 responded 'yes and no', and 337 parents provided a statement in support of their answer. The proposition responses illustrated three themes: ready access to information and advice; reduces isolation; and, staying in touch with family and friends . Cautionary responses described three themes: information but conflicting and judgemental; connection but potential for isolation ; and, in touch but negative social comparison. Online information, support and networks can represent a paradox for parents of young children. Highlights: Online communication sources help to support families with young children. Online benefits: information and advice, reduces isolation, staying in touch. Cautionary online views – face-to-face is better than online. Online cautions: conflicting, judgemental, isolation potential, social comparison.